A dynamic N6-methyladenosine methylome regulates intrinsic and acquired resistance to tyrosine kinase inhibitors. Issue 11 (November 2018) - Yan, Fei; Al-Kali, Aref; Zhang, Zijie; Liu, Jun; Pang, Jiuxia; Zhao, Na; He, Chuan; Litzow, Mark; Liu, Shujun
Abstract N 6 -methyladenosine (m6 A) on mRNAs is critical for various biological processes, yet whether m6 A regulates drug resistance remains unknown. Here we show that developing resistant phenotypes during tyrosine kinase inhibitor (TKI) therapy depends on m6 A reduction resulting fromFTO overexpression in leukemia cells. This deregulated FTO-m6 A axis pre-exists in naïve cell populations that are genetically homogeneous and is inducible/reversible in response to TKI treatment. Cells with mRNA m6 A hypomethylation andFTO upregulation demonstrate more TKI tolerance and higher growth rates in mice. Either genetic or pharmacological restoration of m6 A methylation through FTO deactivation renders resistant cells sensitive to TKIs. Mechanistically, the FTO-dependent m6 A demethylation enhances mRNA stability of proliferation/survival transcripts bearing m6 A and subsequently leads to increased protein synthesis. Our findings identify a novel function for the m6 A methylation in regulating cell fate decision and demonstrate that dynamic m6 A methylome is an additional epigenetic driver of reversible TKI-tolerance state, providing a mechanistic paradigm for drug resistance in cancer.